Types and biological effects of titanium alloys in prosthodontics - Atanas Chonin; Radka Cholakova; Zlatina Tomova; Angelina Vlahova; Mariana Dimova-Gabrovska (Folia Medica)
Recent EU regulations recommend restriction of the use of medical devices in which cobalt content exceeds 0.1%. Commercially pure titanium (cpTi) and titanium alloys appear to be excellent alternatives to cobalt-based alloys in the fields of implantology and prosthodontics. The narrative review summarizes the structure and types of titanium alloys and the methods of their processing. The high biocompatibility of titanium is explained in terms of corrosion, ion release, and interaction with the biological environment. An analysis of existing studies on the mechanical properties of titanium prosthetic restorations is presented, and future perspectives are outlined.